Effect of a post-polymerization treatments on the flexural strength and vickers hardness of reline and acrylic denture base resins - Seo, Rosangela Seiko; Vergani, Carlos Eduardo [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Pavarina, Ana Claudia [UNESP]; Machado, Ana Lucia [UNESP] (FapUNIFESP (SciELO), 2007)
This study evaluated the effect of water-bath and microwave post-polymerization treatments on the flexural strength and Vickers hardness of four autopolymerizing reline resins (Duraliner II-D, Kooliner-K, Tokuso Rebase Fast-TR and Ufi Gel Hard C-UGH) and one heat-polymerized acrylic resin (Lucitone 550-L), processed using two polymerization cycles (short cycle - 90 minutes at 73°C and 100°C for 30 minutes; and long cycle - 9 hours at 71°C). For each material, thirty specimens (64 x 10 x 3.3 mm) were made and divided into 3 groups (n=10). Specimens were tested after: processing (control group); water-bath at 55°C for 10 minutes (reline materials) or 60 minutes (L); and microwave irradiation. Flexural strength tests were performed at a crosshead speed of 5 mm/min using a three-point bending device with a span of 50 mm. The flexural strengths values were calculated in MPa. One fragment of each specimen was submitted to Vickers hardness test. Data were analyzed by 2-way ANOVA followed by Tukey's HSD test (α=0.05). L microwaved specimens (short cycle) exhibited significantly higher flexural strength means than its respective control group (p<0.05). Water-bath promoted a significant increase (p<0.05) in flexural strength of K and L (long cycle). The hardness of the tested materials was not influenced by the post-polymerization treatments. Post-polymerization treatments could be used to improve the flexural strength of some materials tested.
Keywords: Acrylic resins; Denture liners; Hardness; Microwaves